Evaluation implementation growth monitoring and promotion: a case study East Lampung district - Kamilah, Kiki; Herawati, Dewi Marhaeni Diah; Indraswari, Noormarina (International Journal of Public Health Science (IJPHS), 2025)
The implementation of growth monitoring and promotion (GMP), which functions to monitor the growth and development of toddlers, is carried out by integrated service post community health volunteers (CHVs) (in Indonesia called Posyandu), allegedly has not been implemented properly. This research aimed to evaluate the implementation of GMP, its barriers, and supporting factors. The research design is concurrent mixed methods. Quantitative data collection was carried out using GMP practice observation sheets with a sample of 30 CHVs. GMP practice observations were carried out by three observers and the results were analyzed using multi facet Rasch measurement (MFRM). Qualitative data was collected through in-depth interviews and focus group discussion (FGD) with 27 informants. The research results show that GMP practices in the components of growth measurement, plotting measurement results, interpretation of growth indicators, and counseling still need to be improved. Barriers to implementing GMP are human resources, facilities, and infrastructure, lack of motivation, attitude of mothers of toddlers, inadequate capacity of CHV Posyandu, and lack of village government support. Supporting the implementation of GMP is the participation, monitoring, and role of CHVs in human development. The research concludes that the practice of implementing GMP in these four components is considered not optimal. It is recommended that Posyandu CHVs need to increase their capacity in implementing GMP so that the growth and development of children under five can be properly monitored to prevent early malnutrition and stunting.